One‐year efficacy and safety of a fixed combination of insulin degludec and liraglutide in patients with type 2 diabetes: results of a 26‐week extension to a 26‐week main trial. Issue 10 (1st July 2015) - Gough, S. C. L.; Bode, B. W.; Woo, V. C.; Rodbard, H. W.; Linjawi, S.; Zacho, M.; Reiter, P. D.; Buse, J. B.
<x xml:space="preserve">Abstract</x> Aims To confirm, in a 26‐week extension study, the sustained efficacy and safety of a fixed combination of insulin degludec and liraglutide (IDegLira) compared with either insulin degludec or liraglutide alone, in patients with type 2 diabetes. Methods Insulin‐naïve adults with type 2 diabetes randomized to once‐daily IDegLira, insulin degludec or liraglutide, in addition to metformin ± pioglitazone, continued their allocated treatment in this preplanned 26‐week extension of the DUAL I trial. Results A total of 78.8% of patients (1311/1663) continued into the extension phase. The mean glycated haemoglobin (HbA1c) concentration at 52 weeks was reduced from baseline by 1.84% (20.2 mmol/mol) for the IDegLira group, 1.40% (15.3 mmol/mol) for the insulin degludec group and 1.21% (13.2 mmol/mol) for the liraglutide group. Of the patients on IDegLira, 78% achieved an HbA1c of <7% (53 mmol/mol) versus 63% of the patients on insulin degludec and 57% of those on liraglutide. The mean fasting plasma glucose concentration at the end of the trial was similar for IDegLira (5.7 mmol/l) and insulin degludec (6.0 mmol/l), but higher for liraglutide (7.3 mmol/l). At 52 weeks, the daily insulin dose was 37% lower with IDegLira (39 units) than with insulin degludec (62 units). IDegLira was associated with a significantly greater decrease in body weight (estimated treatment difference, −2.80 kg, p < 0.0001) and a 37% lower rate of hypoglycaemia compared with insulin degludec. Overall, all treatments were well tolerated and no new adverse events or tolerability issues were observed for IDegLira. Conclusions These 12‐month data, derived from a 26‐week extension of the DUAL I trial, confirm the initial 26‐week main phase results and the sustainability of the benefits of IDegLira compared with its components in glycaemic efficacy, safety and tolerability.